Social Inequality аs а Problem оf Russian Economic Strategy - L. M. Grigoryev; V. A. Pavlyushina (Мир новой экономики, 2018)
Inequality as a development issue came to the central field of scientific interests in the world in the middle of the 20th century. Recently the international community recognized the importance of the problem by including it as one of the goals in the UN2015 agreement on the goals of sustainable development. The Russian inequality was formed during the transitional crisis of the 1990s mostly due to the fall in GDP by 43% and the specifics of privatization. In 2000s social inequality is marked by rigidity, despite economic growth. Since significant inequality adversely affects the growth and society, its decline is important in the long term and should become a part of the country’s strategy in the future.